Discursive Practices in Teachers' Lesson Plan Documents: A Critical Discourse Analysis Study of Pedagogy and Ideology in Learning - HERDIAWAN, RAMA DWIKA; Nurhidayah, Yayah; Asteka, Pipik; Pamungkas, Trian; Agustin, Hilda Muthia (Journal of English Education and Teaching, 2025)
This study examines English lesson plans as outlined by high school educators in the country of Indonesia in relation to the plans’ language as it concerns the key components of Critical Discourse Analysis (CDA). The research takes on a qualitative approach using Critical Discourse Analysis (CDA) to look into the teaching and ideological aspects embedded in lesson plans of Indonesian EFL teachers. Unlike the lesson plans of other countries, Indonesian lesson plans are not devoid of ideologies. They contain the contrasting ideologies of student autonomy and openness, multicultural teaching, and modern methods and tools of teaching. Including Project Based Learning (PBL), Social Emotional Learning (SEL), and Culturally Responsive (CRT) teaching demonstrates more inclusiveness and flexibility Then there is the Profil Pelajar Pancasila and the Pancasila state ideology which is sheer ethical and nationalist moralism blended with everyday teaching. The use of Multimodal and other forms of assessment shows the targets set are for the learners to demonstrate critical, collaborative, and digital skills. The inquiry has established how through the analysis of documentary evidence and accounts of interviews, teachers construct and interpret the language of professional theory. The findings hence contribute to knowledge in that the formulation of lesson plans is not purely mechanical, rather, it is an arena where beliefs are contested and agency is exercised in the EFL context.